1996
DOI: 10.1002/(sici)1096-9861(19960226)366:1<134::aid-cne9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of neurotransmitters utilized by neurons in the rostral interstitial nucleus of the medial longitudinal fasciculus (riMLF) that project to the oculomotor and trochlear nuclei in the cat

Abstract: The rostral interstitial nucleus of the medial longitudinal fasciculus (riMLF) contains excitatory and inhibitory burst neurons that are related to the control of vertical and torsional eye movements. In the present study, light microscopic examination of the immunohistochemical localization of amino acid neurotransmitters demonstrated that the riMLF in the cat contains overlapping populations of neurons that are immunoreactive to the putative inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…The present study confirms the observation made in cat and rat that the riMLF is highlighted with PAVimmunostaining (Spencer and Wang, 1996;Celio 1990). Moreover, it is shown that the premotor saccadic burst neurons themselves in the riMLF are PAV immunoreactive, and this finding was taken as evidence that parvalbumin can be used as a marker for premotor burst neurons.…”
Section: Trans-synaptic Labelling In the Rimlfsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study confirms the observation made in cat and rat that the riMLF is highlighted with PAVimmunostaining (Spencer and Wang, 1996;Celio 1990). Moreover, it is shown that the premotor saccadic burst neurons themselves in the riMLF are PAV immunoreactive, and this finding was taken as evidence that parvalbumin can be used as a marker for premotor burst neurons.…”
Section: Trans-synaptic Labelling In the Rimlfsupporting
confidence: 93%
“…It comes from stimulation studies that evoke monosynaptic inhibitory postsynaptic potentials in the trochlear (Schwindt et al, 1974) and oculomotor nucleus Shiraishi, 1983, 1985), although it cannot be excluded that iC neurons were stimulated. Anterograde and retrograde double-labelling experiments revealed GABAergic neurons in the riMLF that project to the motoneurons in the oculomotor and trochlear nuclei of the cat (Spencer and Wang, 1996), although no such GABAergic projection was seen in monkey (Carpenter et al, 1992).…”
Section: Trans-synaptic Labelling In the Rimlfmentioning
confidence: 99%
See 2 more Smart Citations
“…The oculomotor nucleus and the trochlear nucleus receive afferents from the rostral interstitial nucleus of the medial longitudinal fasciculus (GABAergic and glutamatergic; Refs. 1180,1335) and interstitial nucleus of Cajal (654). A small number of neurons in the locus coeruleus, trigeminal sensory complex and olivary pretectal nucleus project to the oculomotor nucleus (191,455,646).…”
Section: B Afferent Projections To Orofacial Motor Nucleimentioning
confidence: 99%